THE ROLE OF DIGITAL MEDIA IN DEVELOPING AN ONLINE ANATOMY COURSE FOR THE ACQUISITION OF PRE-SERVICE SCIENCE TEACHERS' HEALTH LITERACY - Handan Ürek (Інформаційні технології і засоби навчання)
In the Pandemic, online learning was conducted after the suspension of face-to-face instruction at the educational institutions to eliminate the spread of the disease. Besides, online learning can also be an effective way to carry out education after natural disasters such as earthquakes. This study aimed to detect the effectiveness of an online anatomy course enriched with digital media news on pre-service science teachers’ course attitudes and health literacy after two major earthquakes hit the east and southeast of Turkey in 2023. In this direction, a single group pre-test – post-test weak experimental design was conducted with the attendance of 25 senior science education students who studied at a governmental university in Turkey. Data was collected with Attitudes towards Anatomy Course Scale and Health Literacy Scale. The study lasted for one semester and included data collection and instruction process on an online learning platform. The instruction process covered the systems in human body. Each course began with the examination of several digital media news regarding the focus of the course. Afterwards, the course content was presented to the students and the course ended with the evaluation of the subject with the help of Web 2.0 tools. Collected data was analyzed quantitatively with SPSS 26.0. According to the results, a significant increase was determined both in pre-service teachers’ mean anatomy course attitudes and health literacies. Besides, detailed analyses indicated significant improvements in the course attitudes and health literacies of three of four subscales of the instruments. It is recommended to implement a similar instructional design to sustain anatomy education during online learning for undergraduate students in different programs. Also, adapting such a course design to face-to-face applications might make contributions to the development of well-equipped pre-service teachers in addition to sustaining healthy young individuals and a healthy society.